Nepal - Country Environmental Analysis : Strengthening Institutions and Management Systems for Enhanced Environmental Governance - World Bank (Washington, DC, 2012)
The main objective of the Country Environmental Analysis (CEA) in Nepal is to identify opportunities for enhancing the overall performance of select environmental management systems through improvements in the effectiveness of institutions, policies, and processes. CEA has been built upon the following three primary study components: (a) an examination of the environmental issues associated with infrastructure development, focusing on the Environmental Impact Assessment (EIA) process in priority growth sectors; (b) an analysis of environmental issues linked to rapid urbanization, focusing on the growing problems of solid waste, poor air quality, and industrial pollution, and the resulting impacts on environmental health; and (c) an analysis of the policy and institutional underpinnings related to key environmental management systems at the national and local levels. This report provides the basis for a discussion of the challenges and options facing Nepal in regard to improving the performance of key environmental management systems and institutions to support its growth and poverty alleviation agenda.